Digital Governance: Optimizing Transparency And Innovation In Village-Owned Enterprises Through Digital Transformation - Ghofar, Abdul; Hakim, Abdurrahman; Islam F, Muhammad Fajrul; Firdaus, Muhammad Akmal (Journal of Innovation and Applied Technology, 2026)
The rural economy is driven strategically by Badan Usaha Milik Desa (BUMDes). Insufficient understanding of Good Corporate Governance (GCG) principles, along with the limited use of modern technology, are the aims why this study was conducted at BUMDes Tegalweru. Hindering both business development and service innovation, trigger this community service to tackle them through the implementation of digital governance employing the development of a website-based management information system. To assess the participants’ knowledge, attitudes, and skills; pre-test and post-test were conducted. The results indicate that there is a great increase in three competence aspects. Prior to the program, 15 participants (60%) did not understand the concepts. However, once the program was conducted, 16 participants (64%) understand the concepts. This denotes that the implementation of a digital governance system, combined with intensive training, effectively increase transparency, accountability, and community participation, ultimately supporting the realization of a professional and sustainable BUMDes.